Heterogeneous Integrations - Lau, John H. (Springer Nature Singapore : Imprint: Springer, 2019)
Heterogeneous integration uses packaging technology to integrate dissimilar chips, LED, MEMS, VCSEL, etc. from different fabless houses and with different functions and wafer sizes into a single system or subsystem. How are these dissimilar chips and optical components supposed to talk to each other? The answer is redistribution layers (RDLs). This book addresses the fabrication of RDLs for heterogeneous integrations, and especially focuses on RDLs on: A) organic substrates, B) silicon substrates (through-silicon via (TSV)-interposers), C) silicon substrates (bridges), D) fan-out substrates, and E) ASIC, memory, LED, MEMS, and VCSEL systems. The book offers a valuable asset for researchers, engineers, and graduate students in the fields of semiconductor packaging, materials sciences, mechanical engineering, electronic engineering, telecommunications, networking, etc.